2020
DOI: 10.18551/rjoas.2020-01.13
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Internal Factors on Business Performance: A Resources Based View of Mushroom Sme in Indonesia

Abstract: Mushrooms are one of the leading agroindustry products. This is not separated from the fact that people will be more aware of consuming mushrooms for health purposes. The high demand causes the flourishing of the mushroom processing industry, including in the Malang area. Because of improving the quality of mushroom products, MSME mushroom processors need to improve business performance. Superior business performance can be achieved with successful competitive advantage. Competitive advantage are factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Even in the most current research, this way of looking at resources as the main source of competitive advantage continues to be the starting point for studying the importance of resources in companies (Ardaneswari et al , 2020). This link between resources and the search for competitive advantage is increasingly pointed out as one of the main strategies for companies to succeed and Mulyono (2013) even mentions that the core of the current RBV theory is even the competitive advantage, being it the way to measure the importance of resources in companies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in the most current research, this way of looking at resources as the main source of competitive advantage continues to be the starting point for studying the importance of resources in companies (Ardaneswari et al , 2020). This link between resources and the search for competitive advantage is increasingly pointed out as one of the main strategies for companies to succeed and Mulyono (2013) even mentions that the core of the current RBV theory is even the competitive advantage, being it the way to measure the importance of resources in companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study emphasises the need for companies to know how to organise themselves to use the differentiated resources in their favour. Ardaneswari et al (2020) also concluded that tangible resources and the company's ability to manage resources influence achieving competitive advantage. In the same research, they could not find the importance of intangible resources.…”
Section: Mrjiam 203mentioning
confidence: 99%